(untitled) (Journal of NELTA, 2022)
Students are often afraid of writing tasks, regardless of whether they are writing in their own native language or are second language writers. I share examples of my own writing experiences and struggles, and then I argue how writing can be demystiﬁ ed, offering some strategies towards advancing one’s writing skills: understanding writing, doing free writing, identifying writing weaknesses, practicing enormously, visualizing purpose and audience, revising writing, articulating writer’s own voice, obtaining feedback, reﬂecting on own writing, and embracing mimesis approach. I discuss the strategies drawing on ideas from renowned writing theorists, including Elbow (1998), Harris (2006), Vilardi and Chang (2009), and Adler-Kassner and Wardle (2016), etc. This paper is particularly relevant to early career ELT teachers to understand and demystify the student writing process; however, it might also be helpful for any academic level of students to advance their writing.